The Effect of Exchange Rate, Tunneling Incentive, and Effective Tax Rate on Transfer Pricing in Multinational Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 Period - Pricillia Yoanda; Latersia Br. Gurusinga; Hermawan Sutanto (SEAN Institute, 2026)
This study aims to determine and analyze the effect of exchange rate, tunneling incentive, and effective tax rate on transfer pricing in multinational manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. This research is quantitative research using secondary data obtained from financial statements published through the official website of the Indonesia Stock Exchange (Indonesia Stock Exchange). The population used in this study consisted of all multinational manufacturing companies listed on the IDX during the 2020–2024 period, totaling 231 companies. The sampling technique used in this research was purposive sampling. Based on several predetermined criteria, 16 companies were selected, resulting in a total of 80 observation data. The data analysis techniques used were descriptive statistics, classical assumption tests, multiple linear regression analysis, and hypothesis testing using IBM SPSS 25. The results of the study show that partially, exchange rate does not have a significant positive effect on transfer pricing, tunneling incentive has a significant positive effect on transfer pricing, while effective tax rate does not have a significant negative effect on transfer pricing. Simultaneously, the variables of exchange rate, tunneling incentive, and effective tax rate have a significant effect on transfer pricing.